The History Book - Published by Dorling Kindersley Limited (London Dorling Kindersley Limited, 2016)
The History Book tackles big historical ideas with stunning visuals, key quotes, and important themes that are woven throughout world history. Discover events from the assassination of Caesar to World War I and see the people and events come to life with The History Book, perfect for students, adults, or anyone who wants to understand our fascinating past.
Include Index, Glossary and Acknowledgment
Keywords: World history -- Middle Ages -- Evolution